MANAJEMEN DANA BANTUAN OPERASIONAL SEKOLAH DI SEKOLAH MENENGAH PERTAMA BRUDER SINGKAWANG - yarso, Herman; Amin, Maswardi M; Chiar, M. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract The management of School Operational Assistance Grant (BOS) at school level based on BOS technical instructions from the minister of education and culture of Republic Indonesia. The purpose of this research is to describe planning, organizing, actuating and monitoring the school operational assistance grant conducted at SMP Bruder Singkawang in order to find out the management process that have done. This study used a descriptive qualitative approach with a case study design and data collection technique based on interviews, observation and documentation. The planning of school operational assistance grant is realized in the form of a school activity and budget plan (RKAS) compiled in a meeting by principal, treasurers, school committees and teachers. The programs in the school activity and budget plan (RKAS) refers to the results of the report on Education Quality Improvement (PMP). The mechanism of school operational assistance distribution has been integrated with the application of basic education data (DAPODIK). The organizing of SMP Bruder Singkawang School Operational Assistance Team based on decree number: 422/009 / SMP.BR / TUK / 2018 dated January 16, 2018. Based on 10 components of financing in BOS technical instructions, 8 components can be realized with school operational assistance grants, while the 2 other components, namely financing new student admission activities and purchasing / maintenance of multilearning tools using foundation grants. Based o the Eight BOS financing standards, the most conspicuous difference betwen plans dan realizations are the proccess standard and the management standard. The supervision of school operational assistance grants in SMP Bruder Singkawang has done directly by the principal, the foundation as the school committee and Education Departmen of Singkawang. Meanwhile, the Education Departmen of Singkawang only conducts the administrative supervision. Keywords: Management, School Operational Assistance Grant